The King James conspiracy - DePoy, Phillip (Griffin ; Melia [distributor], 2010)
In 1605, in Cambridge England, a group of scholars brought together to create a definitive English translation of the Bible finds one of its members savagely murdered by unknown hands. Deacon Marbury, the man in charge of this group, seeks outside help to find the murderer, to protect the innocents and their work. But the people who offer to help are not who they claim to be and the man they send to Marbury-Brother Timon-has a secret past, much blood on his hands, and is an agent for those forces that wish to halt the translation itself.